Determinants of traffic accident mortality in Italy, 1997-1999 (Italian Journal of Public Health, 2005)
Traffic accidents represent an important public health issue in Italy. In order to explore the relationshipbetween traffic accident mortality and factors such as road behaviour, vehicles and road characteristics, fourdifferent linear regression models were performed using data from the end of the 1990’s provided by theNational Institute of Statistics (ISTAT) and from the Automobile Club Italia (ACI). In Italy regional differencesin traffic mortality and injury rates can be observed. Strong predictors are the number of motor vehiclescirculating and road length (inversely associated) and the number of new vehicles circulating and suspendeddriving licenses (directly associated).
Keywords: traffic accidents; mortality; regional differences; Italy